al Jawànib al Wathoniyah 'inda al Mufassirìn al Indunisìn bi al Lughoh al Jàwiyah - Fahrudin, Ali; Hadi, Syofyan (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2020)
The nationalistic attitude of some Muslims in Indonesia is questioned because they are considered intolerant of non-Muslims, especially non-Muslims who are nominated to be leaders in a Muslim-majority region. In fact, the tendency to elect a leader is usually motivated by environmental and religious factors, not because of the absence of nationalism and tolerance towards believers of other religions.This article’s purposeisto prove that this nationalism attitude was also owned by Indonesian Islamic scholars in old times, especially local Tafseer(Tafseer is a commentary book of knowledge)scholars in Javanese. This JavaneseTafseer was chosen because it contains native Indonesians wisdom. The method used in this research is a thematic Tafseer method by elaborating on the opinions of Javanese Tafseer scholars on verses related to nationalism. The conclusion of this article reveals that the Javanese Tafseer scholars have very high nationalistic attitudes towards their country. This is reflected in his work which is very prominent in the aspects of love for their homeland, tolerance, and defending the country.